mTORC1 senses glutamine and other amino acids through GCN2 - Figlia, Gianluca; Müller, Sandra; Garcia-Cortizo, Fabiola; Neff, Marilena; Klinke, Glynis; Poschet, Gernot; Teleman, Aurelio A. (The EMBO journal, 2025)
mTORC1 promotes cell growth when nutrients such as amino acids are available. While dedicated sensors relaying availability of leucine, arginine and methionine to mTORC1 have been identified, it is still unclear how mTORC1 senses glutamine, one of its most potent inducers. Here, we find that glutamine is entirely sensed through the protein kinase GCN2, whose initial activation is not triggered by depletion of glutamine itself, but by the concomitant depletion of asparagine. In turn, GCN2 leads to a succession of events that additively inhibit mTORC1: within 1 h, GCN2 inhibits mTORC1 through the Rag GTPases, independently of its function as an eIF2α kinase. Later, GCN2-mediated induction of ATF4 upregulates Ddit4 followed by Sestrin2, which together cause additional mTORC1 inhibition. Additionally, we find that depletion of virtually any other amino acid also inhibits mTORC1 through GCN2. GCN2 and the dedicated amino acid sensors thus represent two independent systems that enable mTORC1 to perceive a wide spectrum of amino acids.